Risk and protective factors for physical and sexual abuse of children and adolescents in Africa - Meinck, F; Cluver, L; Boyes, M; Mhlongo, E (SAGE Publications, 2014)
There is now conclusive evidence of the major and long-lasting negative effects of physical and sexual abuse on children. Within Africa, studies consistently report high rates of child abuse, with prevalence as high as 64%. However, to date, there has been no review of factors associated with physical and sexual child abuse and polyvictimization in Africa. This review identified 23 quantitative studies, all of which showed high levels of child abuse in varying samples of children and adults. Although studies were very heterogeneous, a range of correlates of abuse at different levels of the Model of Ecologic Development were identified. These included community-level factors (exposure to bullying, sexual violence, and rural/urban location), household-level factors (poverty, household violence, and non-nuclear family), caregiver-level factors (caregiver illness in particular AIDS and mental health problems, caregiver changes, family functioning, parenting, caregiver-child relationship, and substance abuse), and child-level factors (age, disability, physical health, behavior, and gender). These findings identify key associated factors that are potential foci of child abuse prevention interventions. In addition, there is a clear need for further rigorous longitudinal research into predictive factors and culturally relevant interventions.